Major Challenges for EU Tourism Policy: Array - Çankaya Kurnaz, Seda; Kurnaz, Ali (Acta Universitatis Danubius. Relationes Internationales, 2022)
Tourism is the one of the sectors that developing fastest and growing globally in the last thirty years. Because of tourism has affected a wide range of areas, especially economic growth, education, employment, and social development, it has become a critical component of socio-economic development and prosperity for both developed and developing countries. EU member states are among the most important and spearheaded destinations for travellers. Italy, Germany, France and Spain are among the top 10 global destinations in Europe. Even though the tourism sector is an important industry in the EU, tourism industry has encountered some difficulties and challenges in the region. These difficulties force the EU to act together with the member countries. The EU is endeavoring to take better action on tourism because of its positive impact on other industries. In the light of this information the aim of the research is to evaluate the priority of tourism policies of the EU and determine its challenges. The results of the study showed that The EU does not have a common tourism policy that includes common rules, applications and principles between member states. But it doesn't mean that Eu do not have any policies regarding the tourism sector. The EU has many activities under the other policy headings, but it developed in a limited way. Even though there are many challenges that the EU must overcome, it's clear that creating a common tourism policy between member states has a vital importance for the EU economy and society.